Rosja jako tekst w prozie Wiktora Pielewina - Tomasz Nakoneczny (Studia Rossica Posnaniensia)
The article presents the work of Victor Pelevin, one of the most famous contemporary Russian writers, in the context of changes in literary communication. The writer uses postmodern techniques and strategies (intertextuality, decanonization, heterogeneity) and traditional cultural motifs and themes (Russian and foreign) to compensate literature for the loss of its metaphysical attributes and authority of high art.